ANALISIS STRATEGI PENGEMBANGAN BISNIS UMKM MOESLEM SQUARE NGAWI - Andi Andi Triyawan; Amin Fitria (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2019)
The Aim of this research are to determine the strategy of the Moeslem Square MSME business development of the big family of Mr. H. Ahmad Subkhi Djuwigna and to know Islamic business ethics in the business development strategy of the big family Mr. H. Ahmad Subkhi Djuwigna. The Business of Mr. H. Ahmad Subkhi Djuwigna is a fast growing business in Muslim fashion products that are external and internal strategies of business development. The branch of bussiness like Aluminum and Glass Mabrur along with its branches, mabrur boutiques, as-salaam boutiques, kalila boutiques, and nirmala boutiques that have been known by many people in the city of Ngawi. This is because this business has a very Islamic development method and its own characteristics and always provides the best quality of goods and services for its customers. This research is a qualitative descriptive study. This research was conducted in a business location in order to obtain data using primary data sources through interviews, observation and documentation, and to support this research also used secondary data taken from books, journals and other sources related to Islamic business ethics in business development strategies extended family Mr. H. Ahmad Subkhi Djuwigna. In the business development strategy there are external factors, namely economic, social, demographic culture, environment, government, technology and competitors. In addition there are internal factors in the strategy like management, marketing, finance, products and Human Resourse